From the Periphery to the Centre of Historiography: Paths to Central Europe’s Rural Past - Papathanassiou, Maria (Historein, 2025)
This article deals with concrete historiographical developments in central European social, and more specifically rural, history. During the early 1980s in Vienna, a (new) social or rather socio-cultural history of rural Austria, especially for the time period between the late nineteenth century and the outbreak of the Second World War, moved from the periphery to the centre of historiography, where it was met with a positive response by historians and the public. Thanks primarily to the collection of numerous life records, historical subjects came into the fore of research and new issues were explored under the theoretical and methodological auspices of historiographical trends that were partly native to German-speaking academia, such as 1990s historical anthropology. A multifaceted rural world in its own right has defied the primacy of the industrial and the urban world in old as well as in new forms of social history.